Modification method of proton exchange membrane with high vanadium resistance

By introducing TiO2-SO3H@PMoA nanocomposite into the Nafion membrane, the problem of high vanadium ion permeability of the Nafion membrane in the all-vanadium redox flow battery is solved, achieving both high proton conductivity and low vanadium ion permeability, which is significant. Improved battery efficiency and service life.

CN119361774AActive Publication Date: 2025-01-24山西国润储能科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411494936.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing Nafion films in all-vana flow batteries have limited battery efficiency and service life due to their high vanadium ion permeability, and the modification method is difficult to take into account high proton conductivity and mechanical stability.

Method used

Introduce the TIO2-SO3H@PMOA nano composite material in the Nafion membrane. By synthesizing the hollow TIO2-SO3H nanomal material and reacting with the phosphate, the hollow TiO2-SO3H composite material of PMOA is prepared to form a modification in the Nafion solution into the Nafion solution. Proton exchange membrane.

Benefits of technology

It significantly improves the proton conductivity, enables the proton conductivity to reach 200 ~ 300ms/cm, and at the same time reduces the ion ion penetration rate to 1 × 10-9cm2/s, which improves the Kuron efficiency, energy efficiency and service life of the full-liquid stream battery Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361774A_ABST
    Figure CN119361774A_ABST
Patent Text Reader

Abstract

The invention relates to the field of all-vanadium redox flow batteries, and discloses a modification method of a proton exchange membrane with high vanadium resistance, which comprises the following steps: synthesizing a hollow TiO2-SO3H nano material: mixing and dissolving tetrabutyl titanate (TNB) and polyvinylpyrrolidone (PVP) in a solvent of ethanol and anhydrous acetic acid, violently stirring and calcining to obtain solid TiO2; the preparation method comprises the following steps: carrying out hydrothermal reaction on solid TiO2 in a NaOH solution to form hollow TiO2; and carrying out sulfonation reaction on the hollow TiO2 in an H2SO4 solution. The TiO2-SO3H-coated PMoA nano composite material is introduced into the Nafion membrane, so that the proton conductivity is remarkably improved, the proton conductivity of the membrane reaches 200-300 mS / cm, the overall vanadium resistance performance of the membrane is ensured while efficient proton conduction is kept, and the membrane is suitable for being applied to an all-vanadium redox flow battery under high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of all-vanadium liquid flow batteries, in particular to a method for modifying a proton exchange membrane with high vanadium resistance performance. Background Art

[0002] All-vanadium redox flow battery (VRB) is an important energy storage system. It is widely used in large-scale energy storage scenarios because of its renewable, environmentally friendly and long life characteristics. As the core component of all-vanadium redox flow battery, proton exchange membrane mainly plays the role of separating positive and negative electrolytes and promoting proton conduction, which directly determines the coulombic efficiency, energy efficiency and service life of the battery. At present, Nafion membrane is the most widely used proton exchange membrane material with good proton conductivity, but its high vanadium ion permeability limits the overall performance of the battery.

[0003] The proton conductivity of Nafion membrane comes from the hydrophilic ion channels formed inside it, which can effectively conduct protons. However, the ion cluster structure of Nafion membrane is large, and vanadium ions can easily diffuse to the other side of the membrane through these channels, resulting in cross-contamination of positive and negative electrolytes, which seriously reduces the coulombic efficiency and voltage efficiency of the battery. In addition, although some studies have improved the vanadium resistance of Nafion membrane by doping with inorganic nanomaterials, these modification methods usually sacrifice proton conductivity and cannot take into account both high proton conductivity and low vanadium ion permeability.

[0004] In the prior art, the Nafion membrane has a high vanadium ion permeability, which limits the efficiency and service life of the all-vanadium flow battery. Although the prior art proposes to dope inorganic materials in the membrane to enhance the vanadium resistance, these modification methods often fail to effectively balance proton conductivity and mechanical stability. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for modifying a proton exchange membrane with high vanadium resistance. The present invention introduces a TiO2-SO3H@PMoA nanocomposite material into a Nafion membrane, thereby significantly improving the proton conductivity to 200-300 mS / cm and significantly reducing the vanadium ion permeability to 1×10 -9 cm 2 / s, the membrane has excellent vanadium resistance and proton conductivity, which effectively solves the problem of high vanadium ion permeability, proton conductivity and mechanical stability of existing Nafion membrane, and significantly improves the coulombic efficiency, energy efficiency and service life of all-vanadium liquid flow battery.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for modifying a proton exchange membrane with high vanadium resistance performance, comprising the following steps:

[0007] Synthesize hollow TiO2-SO3H nanomaterials, including:

[0008] Tetrabutyl titanate (TNB) and polyvinyl pyrrolidone (PVP) were mixed and dissolved in a solvent of ethanol and anhydrous acetic acid, stirred vigorously and calcined to obtain solid TiO2;

[0009] Solid TiO2 is subjected to hydrothermal reaction in NaOH solution to form hollow TiO2;

[0010] The hollow TiO2 is subjected to sulfonation reaction in H2SO4 solution to obtain hollow TiO2-SO3H;

[0011] The hollow TiO2-SO3H composite material anchored with PMoA was prepared by reacting the hollow TiO2-SO3H with phosphomolybdic acid (PMoA) solution;

[0012] The prepared hollow TiO2-SO3H@PMoA nanocomposite was doped into Nafion solution, and a modified proton exchange membrane was obtained through stirring, film forming and drying steps.

[0013] Preferably, the synthesis of hollow TiO2-SO3H nanomaterials further comprises the following specific steps:

[0014] 5 g of TNB and 2 g of PVP were added to a mixed solvent of 10 g of ethanol and 2 g of anhydrous acetic acid, and stirred vigorously at room temperature for 4 h to obtain a yellow solution;

[0015] Centrifuging the solution to obtain a solid material;

[0016] The solid material was placed in a muffle furnace, heated to 320° C. at a heating rate of 5° C. / min, and calcined in air for 6 h to obtain solid TiO 2 .

[0017] Preferably, the centrifugal separation of the solution specifically includes: a centrifugal speed of 10000 rpm and a duration of 10 min.

[0018] Preferably, the average particle size of the solid TiO2 particles after calcination is 50 to 100 nm.

[0019] Preferably, the centrifugal separation of the solution further comprises the step of subjecting the solid TiO2 to a hydrothermal reaction in an aqueous NaOH solution, the step specifically comprising:

[0020] 0.1 g of solid TiO2 was soaked in 1 M NaOH solution;

[0021] Transferring the soaked solid TiO2 to a stainless steel autoclave lined with polytetrafluoroethylene;

[0022] Hydrothermal reaction at 180 °C for 36 h;

[0023] The obtained product was repeatedly washed with deionized water until the pH value reached 7.

[0024] Preferably, the calcination further comprises:

[0025] Add 0.1g hollow TiO2 into 10MH2SO4 solution;

[0026] Heat at 60°C for 8h;

[0027] The mixture was washed repeatedly with deionized water until the pH value reached 7.

[0028] Preferably, the formation of the hollow TiO2 comprises:

[0029] 5 g of PMoA was dissolved in 45 g of N,N-dimethylformamide (DMF) solution and stirred for 5 hours to obtain a 10% PMoA solution;

[0030] Using a vacuum impregnation method, 0.08 g of hollow TiO2-SO3H nanomaterials was immersed in the 10% PMoA solution;

[0031] Keep it in a vacuum oven at 70℃ for 4h to anchor PMoA on the TiO2-SO3H surface.

[0032] Preferably, the vacuum degree of the vacuum impregnation step is controlled below 0.05 MPa.

[0033] Preferably, the formation of the hollow TiO2-SO3H comprises:

[0034] Add 5 g of Nafion resin into 95 g of N,N-dimethylformamide solution;

[0035] Heat and stir in a water bath at 150 °C for 5 h to ensure that the Nafion resin is completely dissolved;

[0036] 0.04 g of hollow TiO2-SO3H@PMoA nanomaterials were added to 80 ml of 5% Nafion solution and stirred in a 60 °C water bath for 5 h;

[0037] The uniformly stirred solution was poured into a mold and heated at 100° C. for 6 h to form a film;

[0038] The formed proton exchange membrane is repeatedly rinsed with deionized water to remove residual solvent.

[0039] Preferably, the proton conductivity of the prepared modified proton exchange membrane is 200-300 mS / cm, and the vanadium ion permeability is less than 1×10 -9 cm 2 / s.

[0040] The present invention provides a method for modifying a proton exchange membrane with high vanadium resistance performance. It has the following beneficial effects:

[0041] 1. The present invention significantly improves the proton conductivity by introducing TiO2-SO3H@PMoA nanocomposite material into Nafion membrane, so that the proton conductivity of the membrane reaches 200-300 mS / cm. While maintaining efficient proton conduction, the overall electrochemical performance of the membrane is ensured, which is suitable for all-vanadium liquid flow battery applications under high current density.

[0042] 2. The present invention significantly reduces the vanadium ion permeability through the ion selectivity and physical barrier effect of TiO2-SO3H, and the permeability is as low as 1×10 -9 cm 2 / s, effectively reducing vanadium ion cross-contamination, improving the coulombic efficiency and voltage efficiency of the all-vanadium liquid flow battery, and extending the battery life.

[0043] 3. The proton exchange membrane of the present invention has good mechanical strength and long-term stability, and exhibits excellent corrosion resistance and structural stability in a strong acid environment. Its high efficiency in vanadium resistance and high proton conductivity significantly improve the overall efficiency of the all-vanadium liquid flow battery, making it suitable for long-term stable operation in actual industrial energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for modifying a proton exchange membrane with high vanadium resistance performance, comprising the following steps:

[0047] Synthesize hollow TiO2-SO3H nanomaterials, including:

[0048] 1. Mix tetrabutyl titanate (TNB) and polyvinyl pyrrolidone (PVP) and dissolve them in a solvent of ethanol and anhydrous acetic acid, stir vigorously and then calcine to obtain solid TiO2. First, mix tetrabutyl titanate (TNB) and polyvinyl pyrrolidone (PVP) and dissolve them in a solvent of ethanol and anhydrous acetic acid, and stir vigorously to ensure that the two chemical substances can be fully mixed to form a uniform solution. After the solution is calcined, solid TiO2 particles are obtained. The high temperature during the calcination process causes tetrabutyl titanate to decompose and generate nano-scale TiO2 particles. These particles can form the desired solid form by regulating their structure during the reaction process. This solid structure prepares for the subsequent NaOH solution treatment, and its uniform structural characteristics help to improve the uniformity of the final hollow structure;

[0049] 2. Solid TiO2 is subjected to hydrothermal reaction in NaOH solution to form hollow TiO2. The hollow TiO2 obtained by this step has a large specific surface area and a unique hollow structure, which helps to improve the barrier effect of vanadium ions and provide more active sites for subsequent functionalization. This hollow structure can also reduce the density of the material, making it more evenly distributed in the proton exchange membrane, thereby further optimizing the overall performance of the membrane;

[0050] 3 The hollow TiO2 is subjected to sulfonation reaction in H2SO4 solution to obtain hollow TiO2-SO3H. The sulfonation of hollow TiO2 not only provides ion selectivity for the material, but also blocks the positively charged vanadium ions (V n+ ) through the membrane, thereby significantly reducing the permeability of vanadium ions;

[0051] By reacting hollow TiO2-SO3H with phosphomolybdic acid (PMoA) solution, a hollow TiO2-SO3H composite material anchored with PMoA was prepared. This step effectively maintained the proton donor function of PMoA. At the same time, hollow TiO2-SO3H served as a matrix to further improve the vanadium resistance of the membrane. Through the composite of this material, the proton conductivity was fully maintained, avoiding the problem of decreased proton conductivity in the traditional modification process.

[0052] The prepared hollow TiO2-SO3H@PMoA nanocomposite material was added to the Nafion solution, and a modified proton exchange membrane was obtained through stirring, film forming and drying steps. The modified proton exchange membrane has a significant vanadium ion barrier effect. The introduction of hollow TiO2-SO3H nanomaterials forms a stable structural barrier, which effectively prevents vanadium ions from passing through the membrane. At the same time, the presence of phosphomolybdic acid maintains the proton conductivity of the membrane, ensuring the efficient operation of the battery. Through this modification process, the overall performance of the membrane has been significantly improved, thereby improving the coulombic efficiency and voltage efficiency of the all-vanadium liquid flow battery and extending the battery life.

[0053] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the synthesis of hollow TiO2-SO3H nanomaterials further comprises the following specific steps:

[0054] 5 g of TNB and 2 g of PVP were added to a mixed solvent of 10 g of ethanol and 2 g of anhydrous acetic acid, and stirred vigorously at room temperature for 4 h to obtain a yellow solution. This uniform stirring ensured the uniformity of the reaction solution, which helped to improve the uniformity and structural stability of the subsequently generated TiO2 particles, providing a guarantee for achieving a good nanoscale structure.

[0055] The solution is centrifuged to obtain a solid material. The solvent and impurities that are not involved in the reaction can be effectively removed by centrifugation to obtain pure TiO2 particles. This step ensures the purity of subsequent materials and improves the structural consistency of TiO2.

[0056] The solid material was placed in a muffle furnace, heated to 320°C at a heating rate of 5°C / min, and calcined in air for 6 hours to obtain solid TiO2. The calcination process completely decomposed the organic matter and formed solid TiO2 particles with a stable crystal structure, providing a stable structural foundation. The uniformity and purity of the particles provided favorable conditions for subsequent reactions and improved the mechanical strength and thermal stability of the material.

[0057] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the centrifugal separation of the solution specifically includes: the centrifugal speed is 10000rpm, the duration is 10min, the centrifuge rotates at high speed, and uses centrifugal force to deposit the solid particles in the solution to the bottom of the tube. Especially under high-speed rotation, TiO2 particles are quickly pushed to the bottom of the tube by centrifugal force due to their relatively large mass and form precipitation. Centrifugal speed and time are key parameters affecting the separation effect. The centrifugal speed of 10000rpm can provide sufficient centrifugal force to quickly separate nano-scale TiO2 particles from the solution. The duration of 10min ensures the full sedimentation of the solution during the centrifugation process to avoid the particles from being suspended in the supernatant. After the centrifugation is completed, the solid precipitate in the centrifuge tube is collected, and the supernatant is carefully removed. Through this operation, the solvent and impurities that do not participate in the reaction are removed, ensuring that a high-purity solid material is obtained. In addition, a reasonable combination of centrifugal speed and time also avoids particle aggregation or damage to the structure of the particles, so that the obtained TiO2 particles maintain good dispersibility and nanostructure.

[0058] Please refer to the attached Figure 1In a preferred embodiment of the present invention, the average particle size of the solid TiO2 particles after calcination is 50-100 nm. The particle size of 50-100 nm can provide a sufficiently large surface area for the subsequent sulfonation reaction and ensure that the TiO2 particles are evenly dispersed in the membrane to avoid large particle agglomeration. Particles within this particle size range have high reactivity and can better combine with phosphomolybdic acid (PMoA) in the subsequent process to ensure the integrity of the proton conduction channel.

[0059] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the solution centrifugal separation further comprises the step of subjecting the solid TiO2 to a hydrothermal reaction in an aqueous NaOH solution, the step specifically comprising:

[0060] 0.1g solid TiO2 is soaked in 1M NaOH solution. The NaOH concentration during the soaking process is controlled to 1M, which can ensure the effective dissolution of the inner core without causing excessive damage to the outer structure, thereby maintaining the integrity of the TiO2 shell. The soaking time is closely related to the solution concentration. Reasonable control can avoid excessive damage to the internal and external structures. By soaking solid TiO2 in 1M NaOH aqueous solution, the inner core structure can be effectively dissolved, and the framework of the hollow structure can be initially formed, which ensures the stability of the outer shell and is conducive to the formation of hollow TiO2 in subsequent reactions.

[0061] The soaked solid TiO2 is transferred to a stainless steel autoclave lined with polytetrafluoroethylene. The closed environment of the stainless steel autoclave can generate high pressure under high temperature conditions. Under such conditions, the erosion of the NaOH solution will be significantly enhanced, which helps to further dissolve the inner core of the TiO2 particles. At the same time, the use of polytetrafluoroethylene lining can prevent NaOH from corroding the equipment and extend the service life of the equipment, thereby ensuring the smooth progress of the reaction under high temperature and high pressure conditions, providing a strong alkaline environment and chemical stability, and improving the efficiency of the reaction;

[0062] The hydrothermal reaction was carried out at 180°C for 36 hours. Under this temperature condition, the hollowing of the TiO2 particles was gradually completed, the internal structure was completely eroded, and the outer shell was retained due to its high mechanical strength. The reaction time of 36 hours ensured the full dissolution of the interior of the TiO2 particles, and a uniform and stable hollow structure was obtained. By carrying out the hydrothermal reaction at 180°C for 36 hours, the interior of the solid TiO2 particles could be completely dissolved by NaOH, and finally hollow TiO2 particles with high specific surface area and good structural stability were formed, which helped to improve the reactivity and dispersibility of the material.

[0063] The obtained product is repeatedly washed with deionized water to a pH value of 7. By repeatedly washing with deionized water, the purity of the hollow TiO2 particles is ensured and the pH value is made neutral, which provides excellent basic conditions for the subsequent sulfonation reaction and avoids any alkaline residue that is not completely removed from having an adverse effect on the subsequent reaction.

[0064] Please see attached Figure 1 In a preferred embodiment of the present invention, the calcination further comprises:

[0065] 0.1g of hollow TiO2 was added to a 10MH2SO4 solution. Sulfonic acid groups (SO3H) were successfully introduced onto the surface of hollow TiO2 by sulfonation treatment in 10MH2SO4. This step endowed TiO2 particles with better ion selectivity and significantly enhanced their ability to block vanadium ions while maintaining good proton conductivity.

[0066] Heat at 60°C for 8h. Heat the 10MH2SO4 solution containing hollow TiO2 at 60°C for 8h. This temperature condition can both accelerate the reaction rate and avoid damage to the TiO2 structure caused by high temperature. The heating process promotes the chemical bonding of SO3H groups with the surface of TiO2, allowing the sulfonic acid groups to be more firmly anchored on the surface of TiO2 particles, so that the SO3H groups can be evenly and firmly bonded to the surface of hollow TiO2 to form a stable TiO2-SO3H structure. The heating treatment ensures the full progress of the sulfonation process, so that the modified TiO2 particles have better stability and ion selectivity, especially the vanadium barrier effect in the proton exchange membrane is significantly enhanced;

[0067] Repeatedly washing with deionized water to a pH value of 7 can ensure that there is no excess acid residue on the surface of the TiO2-SO3H particles, and obtain pure and stable materials. This step further ensures the chemical stability and dispersibility of the TiO2-SO3H particles, provides high-quality materials for the subsequent proton exchange membrane modification step, and ensures the vanadium resistance and proton conductivity of the membrane.

[0068] Please see attached Figure 1 In a preferred embodiment of the present invention, the formation of hollow TiO2 comprises:

[0069] Dissolve 5g of PMoA in 45g of N,N-dimethylformamide (DMF) solution and stir for 5 hours to obtain a 10% PMoA solution. Stir for a long time to ensure that PMoA is fully dispersed in the DMF solution to form a uniform and stable solution. This uniform dispersion state can ensure that in the subsequent vacuum impregnation process, PMoA can be evenly anchored on the surface of TiO2-SO3H to improve the proton conductivity. By fully dissolving PMoA in the DMF solution, the uniformity and stability of the solution are ensured, providing a good foundation for the subsequent steps of anchoring PMoA. The high proton conductivity of PMoA can provide an effective proton conduction path in the membrane, which helps to improve the overall performance of the proton exchange membrane;

[0070] Using the vacuum impregnation method, 0.08g of hollow TiO2-SO3H nanomaterials were immersed in a 10% PMoA solution. The vacuum treatment ensured full contact between the TiO2-SO3H surface and PMoA. This method can avoid the problem of uneven solution coverage in the traditional impregnation process and effectively improve the utilization rate of PMoA. PMoA molecules are evenly distributed on the surface of hollow TiO2-SO3H, providing more transmission paths for proton conduction while maintaining the ion selectivity of TiO2-SO3H. The vacuum impregnation method ensures that PMoA molecules can be evenly and stably attached to the surface of TiO2-SO3H, avoiding the problem of uneven coverage of the material during use, and further improving the conductivity of the proton exchange membrane.

[0071] Keep it in a vacuum oven at 70℃ for 4 hours to anchor PMoA on the surface of TiO2-SO3H. This step can effectively accelerate the combination of PMoA and the surface of TiO2-SO3H through the synergistic effect of temperature and vacuum environment to form a stable chemical bond. The temperature condition of 70℃ can not only promote the movement of PMoA molecules and improve the anchoring efficiency, but also will not destroy the structural integrity of TiO2-SO3H. The vacuum environment helps to further remove impurities in the air and ensure that the anchoring process is not affected by the outside world. After 4 hours of treatment, PMoA molecules are firmly anchored on the surface of TiO2-SO3H and are not easy to fall off, ensuring the long-term stability of the nanocomposite material in the proton exchange membrane, thereby improving the performance of the nanocomposite material, ensuring its stable performance in the proton exchange membrane, and improving the conductivity efficiency and ion selectivity without sacrificing structural integrity.

[0072] Please refer to the attached Figure 1In a preferred embodiment of the present invention, the vacuum degree of the vacuum impregnation step is controlled below 0.05MPa. By controlling the vacuum degree below 0.05MPa, it is possible to ensure that the PMoA molecules are evenly and firmly anchored on the TiO2-SO3H surface, avoiding the problem of rapid evaporation of the solution or residual bubbles on the surface of the material under high vacuum. This step improves the surface modification effect of the nanomaterial, ensures the uniformity of the distribution of the material in the proton exchange membrane, and further improves the proton conductivity and vanadium resistance of the membrane. In addition, another major advantage of controlling the vacuum degree is to prevent excessive adsorption and material agglomeration. When the vacuum degree is too high, the adhesion of the material surface is too strong, which easily leads to excessive deposition in local areas, resulting in uneven distribution of PMoA and affecting the performance of the material. The appropriate vacuum degree can ensure that the solution evenly covers the TiO2-SO3H surface and improves the performance consistency of the final modified membrane.

[0073] Please see attached Figure 1 In a preferred embodiment of the present invention, the formation of hollow TiO2-SO3H comprises:

[0074] Add 5g of Nafion resin to 95g of N,N-dimethylformamide solution. 95g of N,N-dimethylformamide solution can effectively dissolve Nafion resin and make it evenly distributed in the solution. Nafion is a fluorine-containing proton exchange membrane material with excellent proton conductivity. The dissolved Nafion resin is the basis for preparing the proton exchange membrane. By dissolving Nafion resin in DMF solution, the uniformity and stability of the Nafion membrane matrix can be guaranteed, providing a good solution environment for the dispersion of nanomaterials in subsequent steps, ensuring the overall performance of the proton exchange membrane;

[0075] Heat and stir in a 150°C water bath for 5 hours to ensure that the Nafion resin is completely dissolved. The 150°C water bath temperature is high enough to effectively accelerate the dissolution of Nafion, but will not cause excessive evaporation of the solvent or degradation of the resin. Continuous stirring for 5 hours can prevent the precipitation of the resin in the solution and ensure that the formed solution has a high uniformity. The completely dissolved Nafion solution lays the foundation for the uniform dispersion and membrane formation of nanomaterials in the subsequent steps. By heating and stirring the Nafion solution in a 150°C water bath, the complete dissolution of the resin can be accelerated, the uniformity of the solution can be ensured, and the stable physical and chemical properties of the solution can be ensured, providing good conditions for the subsequent dispersion of nanomaterials and membrane preparation.

[0076] 0.04 g of hollow TiO2-SO3H@PMoA nanomaterials were added to 80 ml of 5% Nafion solution and stirred in a 60°C water bath for 5 h. During this process, the control of temperature and stirring speed is the key to ensure that the nanomaterials are uniformly dispersed in the Nafion solution. The 60°C water bath temperature can maintain the fluidity of the solution and ensure the dispersibility of the nanomaterials, while avoiding excessively high temperatures that lead to agglomeration of the nanomaterials or degradation of the Nafion solution. By stirring at 60°C, the hollow TiO2-SO3H@PMoA nanomaterials are uniformly dispersed in the Nafion solution, ensuring that the composite material is fully combined with the matrix to form a composite material matrix with excellent vanadium resistance and proton conductivity.

[0077] The stirred solution was poured into a mold and heated at 100°C for 6 hours to form a membrane. By heating at 100°C for 6 hours, the membrane can be formed uniformly and densely, forming a proton exchange membrane with stable mechanical strength and good electrical conductivity, providing high-quality membrane samples for subsequent performance tests.

[0078] The proton exchange membrane after membrane formation is repeatedly rinsed with deionized water to remove residual solvent. Repeated rinsing with deionized water can effectively remove residual solvent and impurities, ensure the purity and stability of the proton exchange membrane, and further improve the conductivity and durability of the membrane, so that it has good performance in electrochemical applications.

[0079] Please refer to the attached Figure 1 In a preferred embodiment of the present invention, the proton conductivity of the prepared modified proton exchange membrane is 200-300 mS / cm, and the vanadium ion permeability is less than 1×10 -9 cm 2 / s. Through the synergistic effect of Nafion matrix and TiO2-SO3H@PMoA composite material, the modified proton exchange membrane can reach a high conductivity level of 200-300mS / cm, ensuring the efficient operation of the battery and significantly improving the electrochemical performance of the all-vanadium liquid flow battery. The modified proton exchange membrane has significant vanadium resistance and the vanadium ion permeability is less than 1×10 -9 cm 2 / s, through the physical and chemical synergistic effect of nanomaterials, the membrane effectively prevents the penetration of vanadium ions while maintaining high proton conductivity, thereby improving the efficiency and life of the all-vanadium liquid flow battery, thereby ensuring the efficient and long-term operation of the all-vanadium liquid flow battery and improving the coulombic efficiency and energy efficiency of the battery.

[0080] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0081] Example 1: Preparation of TiO2-SO3H@PMoA nanomaterial

[0082] Preparation of solid TiO2

[0083] 5g of tetrabutyl titanate (TNB) and 2g of polyvinyl pyrrolidone (PVP) were added to a mixed solvent of 10g of ethanol and 2g of anhydrous acetic acid and stirred for 4h to obtain a yellow solution. The solution was centrifuged to obtain a solid material, which was then calcined in air at 320℃ for 6h to obtain solid TiO2.

[0084] Preparation of hollow TiO2

[0085] 0.1 g of solid TiO2 particles were soaked in 1 M NaOH solution, transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 180 ° C for 36 h to form hollow TiO2. Then it was repeatedly washed with deionized water and adjusted to pH 7.

[0086] Preparation of TiO2-SO3H

[0087] The hollow TiO2 particles were immersed in 10MH2SO4 solution, heated at 60°C for 8 h, and then washed repeatedly until the pH value reached 7 to obtain hollow TiO2-SO3H nanomaterials.

[0088] PMoA anchored TiO2-SO3H

[0089] 5 g of phosphomolybdic acid (PMoA) was dissolved in 45 g of N,N-dimethylformamide (DMF) and stirred for 5 h to obtain a 10% PMoA solution. 0.08 g of TiO2-SO3H nanomaterials were immersed in the PMoA solution and kept in a vacuum oven at 70°C for 4 h to anchor PMoA on the surface of TiO2-SO3H.

[0090] Preparation of proton exchange membrane

[0091] 5g Nafion resin was added to 95g N,N-dimethylformamide, stirred and heated in a 150℃ water bath for 5h to ensure that Nafion was completely dissolved. 0.04g TiO2-SO3H@PMoA nanomaterial was added to 80ml 5% Nafion solution, stirred and heated in a 60℃ water bath for 5h. The solution was then poured into a mold and heated at 100℃ for 6h to form a membrane. Finally, the proton exchange membrane was repeatedly rinsed with deionized water to remove residual solvent.

[0092] Performance Testing

[0093] The test results show that the proton conductivity of the proton exchange membrane is 241mS / cm and the vanadium ion permeability is 6.55×10 -10 cm 2 / s.

[0094] Example 2: Changes in modification temperature conditions

[0095] Preparation of TiO2-SO3H Nanomaterials

[0096] The steps are the same as those in Example 1.

[0097] PMoA anchored TiO2-SO3H

[0098] The anchoring procedure of PMoA remained unchanged, but the temperature of the vacuum oven was set to 80 °C and the duration was extended to 8 h to ensure a more secure anchoring of PMoA.

[0099] Preparation of proton exchange membrane

[0100] The process of preparing Nafion solution was the same as that in Example 1, but when introducing TiO2-SO3H@PMoA nanomaterial into Nafion solution, the water bath temperature was lowered to 50°C, the stirring time was maintained for 6 h, and then the film forming temperature was still 100°C, and the heating time was 6 h.

[0101] Performance Testing

[0102] The proton conductivity of the modified proton exchange membrane is 207mS / cm, and the vanadium ion permeability is 6.82×10 -10 cm 2 / s.

[0103] Example 3: Modification under different sulfonation conditions

[0104] Preparation of TiO2-SO3H

[0105] 0.1 g of hollow TiO2 particles were added to 15 M H2SO4 solution, heated at 60 °C for 8 h, and then repeatedly washed with deionized water until the pH was 7.

[0106] PMoA anchored TiO2-SO3H and preparation of proton exchange membrane

[0107] The anchoring steps of PMoA are the same as those in Example 1, and the preparation steps of the proton exchange membrane are also the same.

[0108] Performance Testing

[0109] The proton conductivity of this modified membrane is 165 mS / cm and the vanadium ion permeability is 7.17×10 -10 cm 2 / s.

[0110] Example 4: Changing TiO2 hydrothermal reaction conditions

[0111] Preparation of solid TiO2

[0112] Same as Example 1.

[0113] Preparation of hollow TiO2

[0114] 0.1 g of solid TiO2 particles were immersed in 1 M NaOH solution, transferred to a stainless steel autoclave, and hydrothermally reacted at 260 °C for 36 h to form hollow TiO2 particles, which were then washed with deionized water and adjusted to pH 7.

[0115] TiO2-SO3H and PMoA anchoring steps

[0116] Same as Example 1.

[0117] Preparation of proton exchange membrane

[0118] The film forming steps are kept consistent with those in Example 1.

[0119] Performance Testing

[0120] Under these conditions, the proton conductivity is 219 mS / cm and the vanadium ion permeability is 6.74×10 -10 cm 2 / s.

[0121] Example 5

[0122] PMoA solution concentration adjustment

[0123] Preparation of TiO2-SO3H Nanomaterials

[0124] Same as Example 1.

[0125] Preparation and anchoring of PMoA solution

[0126] 5 g of PMoA was dissolved in 20 g of N,N-dimethylformamide and stirred for 5 h to obtain a 20% PMoA solution; 0.08 g of TiO2-SO3H nanomaterial was immersed in the 20% PMoA solution and treated in a 70° C. vacuum oven for 4 h.

[0127] Preparation of proton exchange membrane This step is consistent with Example 1.

[0128] Performance Testing

[0129] The proton conductivity is 234 mS / cm and the vanadium ion permeability is 1.17×10 -9 cm 2 / s

[0130] Example 6

[0131] Increase the amount of nanomaterials incorporated

[0132] Preparation of TiO2-SO3H Nanomaterials

[0133] Same as Example 1.

[0134] Preparation of proton exchange membrane

[0135] 0.12 g TiO2-SO3H@PMoA nanocomposite was added to 5% Nafion solution and stirred for 5 h. The film forming steps remained unchanged.

[0136] Performance Testing

[0137] The proton conductivity is 274 mS / cm and the vanadium ion permeability is 5.28×10 -10 cm 2 / s.

[0138] Comparative experiment 1: Proton conductivity test

[0139] Experimental purpose: To evaluate the proton conductivity of the proton exchange membrane of the present invention.

[0140] Experimental setup

[0141] Experimental and control groups:

[0142] Experimental group: using the proton exchange membrane of the present invention, containing the TiO2-SO3H@PMoA nanocomposite material.

[0143] Control group 1: traditional Nafion membrane without any modification.

[0144] Control group 2: Nafion membrane doped with TiO2-SO3H nanomaterials only.

[0145] Control group 3: Nafion membrane doped with PMoA only.

[0146] Test conditions:

[0147] Temperature: Room temperature (25°C)

[0148] Electrolyte: 3mol / LH2SO4

[0149] Test equipment: AC impedance meter

[0150] Film size: 1cm×1cm

[0151] Experimental procedures

[0152] Membrane pretreatment:

[0153] The proton exchange membranes of the experimental group and each control group were cut into small squares of 1 cm × 1 cm and immersed in 3 mol / L H2SO4 solution for 30 min to activate the proton exchange membranes and ensure that all samples were under the same test conditions.

[0154] Resistance measurement:

[0155] Each sample was clamped into a conductivity test device and the resistance value (R) of the membrane was measured using an AC impedance meter.

[0156] Calculate the proton conductivity:

[0157] Proton conductivity is calculated according to the formula:

[0158]

[0159] Where β is the thickness of the membrane (in μm), R is the membrane resistance (in Ω), and α is the proton conductivity unit (mS / cm)

[0160] Repeat the test:

[0161] The membrane was tested three times and the average value was taken to ensure the reliability of the data.

[0162] The comparative experimental data are shown in Table 1:

[0163] Table 1 Proton conductivity data of different proton exchange membranes

[0164]

[0165] From the data in Table 1, we can get:

[0166] The proton conductivity of the experimental group is as high as 245.7 mS / cm, which is about 57% higher than that of the pure Nafion membrane, proving that the present invention optimizes the overall performance of the membrane while maintaining proton conductivity. Control groups 2 and 3 respectively show the effects of TiO2-SO3H and PMoA when used alone, but both are inferior to the performance of the membrane of the present invention, indicating that the present invention achieves the best effect by combining the two materials.

[0167] Comparative experiment 2: Vanadium ion permeability test

[0168] Experimental purpose: By comparing the vanadium ion permeability of the proton exchange membrane of the present invention (experimental group) with that of the existing Nafion membrane and different modified membranes (control group), the significant effect of the present invention in preventing the penetration of vanadium ions is verified.

[0169] Experimental setup

[0170] Experimental and control groups:

[0171] Experimental group: the proton exchange membrane of the present invention, containing the TiO2-SO3H@PMoA nanocomposite material.

[0172] Control group 1 (pure Nafion membrane): traditional Nafion membrane without any modification.

[0173] Control group 2 (only doped with TiO2-SO3H): Only TiO2-SO3H nanomaterials were doped into the Nafion membrane.

[0174] Control group 3 (PMoA only): PMoA was only doped into the Nafion membrane.

[0175] Test conditions:

[0176] Left container: 1.5mol / LMgSO4+3mol / LH2SO4 mixed solution, 50ml.

[0177] Right container: 1.5mol / LVOSO4+3mol / LH2SO4 mixed solution, 50ml.

[0178] Stir continuously to prevent the solution from polarizing.

[0179] The vanadium ion concentration was measured using a UV spectrophotometer.

[0180] Test time: Sampling every 1 hour for 8 hours.

[0181] Experimental procedures

[0182] Membrane installation:

[0183] The proton exchange membrane of the present invention and the membranes of each control group are respectively installed in a vanadium ion permeation test device to ensure that the membranes separate the solutions in the two containers.

[0184] Experiment starts:

[0185] A mixed solution of 1.5 mol / LMgSO4 and 3 mol / LH2SO4 was placed on one side (left side), and a mixed solution of 1.5 mol / LVOSO4 and 3 mol / LH2SO4 was placed on the other side (right side).

[0186] Sample collection:

[0187] Samples were taken from the left container every hour, and the vanadium ion concentration in the solution was measured using an ultraviolet spectrophotometer.

[0188] Data processing:

[0189] The vanadium ion permeability is calculated by the formula:

[0190]

[0191] Where P stands for VO 2 +Permeability coefficient (unit: cm2·s -1 ); L and A represent the thickness and area of ​​the film, respectively (in μm, cm 2 );V R Indicates the volume of the solution in the right reservoir (in cm3 );C L and C R (t) is the VO in the left and right reservoirs 2 +Concentration (mmol / L)

[0192] Repeat the test:

[0193] Each film sample was tested three times and the average value was taken to ensure the data was reliable.

[0194] The comparative experimental data are shown in Table 2:

[0195] Table 2 Data of vanadium ion permeability of different proton exchange membranes

[0196]

[0197]

[0198] From the data in Table 2, we can get:

[0199] The vanadium ion permeability of the experimental group (the present invention) was significantly reduced, reaching 6.05×10 -10 cm 2 / s, compared with the permeability of pure Nafion membrane (7.76×10 -9 cm 2 This indicates that the vanadium resistance of the film of the present invention is significantly improved.

[0200] Comparative experiment 3: All-vanadium liquid flow battery performance test

[0201] Experimental purpose: To verify the advantages of the proton exchange membrane of the present invention in improving battery performance, extending battery life and reducing vanadium ion cross contamination.

[0202] Experimental setup

[0203] Experimental and control groups:

[0204] Experimental group: the proton exchange membrane of the present invention, containing the TiO2-SO3H@PMoA nanocomposite material.

[0205] Control group 1 (pure Nafion membrane): traditional Nafion membrane without any modification.

[0206] Control group 2 (only doped with TiO2-SO3H): Only TiO2-SO3H nanomaterials were doped into the Nafion membrane.

[0207] Control group 3 (PMoA only): PMoA was only doped into the Nafion membrane.

[0208] Test conditions:

[0209] Electrolyte: a mixed solution of 1.5 mol / LVOSO4 and 3 mol / LH2SO4.

[0210] Battery configuration: The working area of ​​each battery group is 25cm 2 .

[0211] Current density: set to 50mA / cm during testing 2 and 100mA / cm 2 .

[0212] Test equipment: Battery test system, used to record parameters such as voltage and current during charging and discharging.

[0213] Test indicators: Coulombic efficiency (CE), voltage efficiency (VE).

[0214] Experimental procedures

[0215] Battery Assembly:

[0216] All-vanadium redox flow battery systems were assembled using different proton exchange membranes (experimental group and control group). The positive and negative electrode solutions of each battery group were the same (1.5 mol / LVOSO4+3 mol / LH2SO4).

[0217] Charge and discharge test:

[0218] At a current density of 50 mA / cm 2 and 100mA / cm 2 Under the conditions of , the charge and discharge cycle of the all-vanadium redox flow battery was carried out. The current and voltage data during charging and discharging were recorded.

[0219] Coulomb efficiency and voltage efficiency calculation:

[0220] Repeat the test:

[0221] Each group of batteries was tested three times and the average value was taken to ensure the reliability of the data.

[0222] The comparative experimental data are shown in Table 3 and Table 4:

[0223] Table 3 All-vanadium liquid flow battery performance test data

[0224]

[0225] Table 3 All-vanadium liquid flow battery performance test data

[0226]

[0227] From the data in Table 3, we can get:

[0228] The present invention (experimental group) showed significant advantages, at 50 mA / cm 2 and 100mA / cm 2 At a high current density of , the coulombic efficiency reached 95.4% and 94.8%, and the voltage efficiency was 85.3% and 84.7%, respectively. This shows that the proton exchange membrane of the present invention can maintain high proton conductivity while inhibiting the penetration of vanadium ions, so that the battery can still maintain efficient charging and discharging under high load conditions.

[0229] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for modifying a proton exchange membrane with high vanadium resistance, characterized in that: The following steps are involved: Synthesize hollow TiO2-SO3H nanomaterials, including: (1) Tetrabutyl titanate (TNB) and polyvinyl pyrrolidone (PVP) are mixed and dissolved in a solvent of ethanol and anhydrous acetic acid, and then calcined after vigorous stirring to obtain solid TiO2; (2) hydrothermally reacting solid TiO2 in a NaOH solution to form hollow TiO2; (3) subjecting the hollow TiO2 to a sulfonation reaction in a H2SO4 solution to obtain a hollow TiO2-SO3H; The hollow TiO2-SO3H composite material anchored with PMoA was prepared by vacuum impregnation of hollow TiO2-SO3H with phosphomolybdic acid (PMoA) solution; The prepared hollow TiO2-SO3H@PMoA nanocomposite was doped into Nafion solution, and a modified proton exchange membrane was obtained through stirring, film forming and drying steps.

2. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The synthesis of hollow TiO2-SO3H nanomaterials further comprises the following specific steps: 5 g of TNB and 2 g of PVP were added to a mixed solvent of 10 g of ethanol and 2 g of anhydrous acetic acid, and stirred vigorously at room temperature for 4 h to obtain a yellow solution; Centrifuging the solution to obtain a solid material; The solid material was placed in a muffle furnace, heated to 320° C. at a heating rate of 5° C. / min, and calcined in air for 6 h to obtain solid TiO 2 .

3. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 2, characterized in that: The centrifugal separation of the solution specifically includes: a centrifugal speed of 10000 rpm and a duration of 10 minutes.

4. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 2, characterized in that: The average particle size of the solid TiO2 particles after calcination is 50 to 100 nm.

5. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The centrifugal separation of the solution further includes the step of subjecting the solid TiO2 to a hydrothermal reaction in an aqueous NaOH solution, the step specifically comprising: 0.1 g solid TiO2 was soaked in 1 M NaOH solution; Transferring the soaked solid TiO2 to a stainless steel autoclave lined with polytetrafluoroethylene; Hydrothermal reaction at 180 °C for 36 h; The obtained product was repeatedly washed with deionized water until the pH value reached 7.

6. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The calcination further comprises: Add 0.1g hollow TiO2 into 10MH2SO4 solution; Heat at 60°C for 8h; The mixture was washed repeatedly with deionized water until the pH value reached 7.

7. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The formation of the hollow TiO2 comprises: Dissolve 5 g of PMoA in 45 g of N,N-dimethylformamide (DMF) solution and stir for 5 h to obtain a 10% PMoA solution; Using a vacuum impregnation method, 0.08 g of hollow TiO2-SO3H nanomaterials was immersed in the 10% PMoA solution; Keep it in a vacuum oven at 70℃ for 4h to anchor PMoA on the TiO2-SO3H surface.

8. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 7, characterized in that: The vacuum degree of the vacuum impregnation step is controlled below 0.05 MPa.

9. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The formation of the hollow TiO2-SO3H comprises: Add 5 g of Nafion resin into 95 g of N,N-dimethylformamide solution; Heat and stir in a water bath at 150 °C for 5 h to ensure that the Nafion resin is completely dissolved; 0.04 g of hollow TiO2-SO3H@PMoA nanomaterials were added to 80 ml of 5% Nafion solution and stirred in a 60 °C water bath for 5 h; The uniformly stirred solution was poured into a mold and heated at 100° C. for 6 h to form a film; The formed proton exchange membrane is repeatedly rinsed with deionized water to remove residual solvent.

10. The method for modifying a proton exchange membrane with high vanadium resistance according to claim 1, characterized in that: The proton conductivity of the prepared modified proton exchange membrane is 200-300 mS / cm, and the vanadium ion permeability is less than 1×10 -9 cm 2 / s.

Citation Information

Patent Citations

  • Preparation method of Nafion / TiO2 nanotube composite diaphragm

    CN107017375A

  • Polyether-ether-ketone-based proton exchange membrane for vanadium battery

    CN110797562A

  • Proton exchange membrane for all-vanadium redox flow battery and preparation method of proton exchange membrane

    CN118610536A

  • Composite membrane for fuel cell and fuel cells incorporating said membranes

    US20050227135A1